OTOMATRIKS: Pengembangan Model Pembangkitan Bilangan Acak Dalam Pembuatan Soal Matriks Secara Otomatis - Meryance Viorentina Siagian; Abdul Karim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Matrices are generally used to represent linear transformations. Matrices are discussed in mathematics courses, and in universities, there are already courses that do discuss matrices, namely matrices and linear transformations. The problem experienced with this matrix is ​​the length of time it takes for teachers/lecturers to make matrix questions and not to mention making steps to solve them. Another problem is that students find it difficult to solve problems about matrices and it is difficult to understand the steps for solving them. From these problems, the solution is to build an application that can create questions about the matrix automatically along with the answers and is equipped with the steps for doing it. The purpose of this research is to make an application for making automatic matrix questions called OTOMATRIKS and the steps for solving them. In this OTOMATRIKS application, a random number generator is applied to generate random numbers which are later needed to be entered into the matrix that will be created. The result of this study is that the Linear Congruent Method can be used to generate random numbers, and to overcome the weakness of this method where the random numbers generated have a pattern and the OTOMATRIKS application can make it easier to make matrix questions that are equipped with the completion steps.